Pengaruh Kecerdasan Emosional, Kemandirian Belajar, dan Kemampuan Berpikir Kritis terhadap Hasil Belajar Peserta Didik di SMA Kecamatan Pallangga: The Influence of Emotional Intelligence, Learning Independence, and Critical Thinking Ability on Student Learning Outcomes at Pallangga District High School - Azazi, Amalia Nur; Hala, Yusminah; Syamsiah, Syamsiah (Anterior Jurnal, 2025)
This research aims to determine the influence of emotional intelligence, learning independence, and critical thinking abilities on learning outcomes for high school students in Pallangga District. This type of research uses ex-post facto research. This research was carried out in January-February 2024 at SMA Negeri Pallangga District. The population in this study were all students in class XI Science at State High Schools in Pallangga District for the 2023/2024 academic year consisting of 2 schools. The sampling technique used in this research is stratified random sampling. The total sample used was 236 students. The research results include: (1)There is an influence of emotional intelligence on the critical thinking abilities of class XI SMAN students in Pallangga District; (2)There is an influence of emotional intelligence on the learning outcomes of class XI SMAN students in Pallangga District; (3)There is an influence of independent learning on the critical thinking abilities of class XI SMAN students in Pallangga District; (4)There is an influence of independent learning on the learning outcomes of class XI SMAN students in Pallangga District; (5)There is an influence of critical thinking skills on the learning outcomes of class XI SMAN students in Pallangga District; (6)There is an indirect influence of emotional intelligence on learning outcomes through the critical thinking abilities of Class XI SMAN students in Pallangga District; (7)There is an indirect influence of learning independence on learning outcomes through the critical thinking skills of Class XI SMAN students in Pallangga District.